2019
DOI: 10.3390/en12020331
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Implementation of Carbon Capture Systems on the Environmental, Energy and Economic Performance of the Brazilian Electricity Matrix

Abstract: This study examined the effect of Carbon Capture and Storage units on the environmental, energy and economic performance of the Brazilian electric grid. Four scenarios were established considering the coupling of Calcium Looping (CaL) processes to capture CO2 emitted from thermoelectric using coal and natural gas: S1: the current condition of the Brazilian grid; S2 and S3: Brazilian grid with CaL applied individually to coal (TEC) and gas (TGN) operated thermoelectric; and S4: CaL is simultaneously coupled to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Conceptually, EEA conducted in this study is a variant of the approach proposed in [58] in which the environmental and economic performance of one of the analysis scenarios (or objects) are used as references for applying the standardization procedure. This logic was applied previously for assessments in water recovery areas [59][60][61], beef production [62], solid waste management [43], and energy resources [63], providing consistent results. As it has been on the market for years, StC has naturally become this standard for the present case.…”
Section: Ecoefficiency Analysis (Eea)mentioning
confidence: 61%
“…Conceptually, EEA conducted in this study is a variant of the approach proposed in [58] in which the environmental and economic performance of one of the analysis scenarios (or objects) are used as references for applying the standardization procedure. This logic was applied previously for assessments in water recovery areas [59][60][61], beef production [62], solid waste management [43], and energy resources [63], providing consistent results. As it has been on the market for years, StC has naturally become this standard for the present case.…”
Section: Ecoefficiency Analysis (Eea)mentioning
confidence: 61%
“…Across the decades, several authors carried out partial or complete LCA of power stations with CCS technology and observed major reduction in terms of GHGs when compared to conventional fossil-fueled power plants. [20][21][22][23][24][25][26] Limited researchers have studied the nationally environmental effects of CCS technology. [27][28][29][30][31][32] Additionally, several authors addressed the complexity and requirements of the LCA technique in general.…”
Section: Value Added Products From Co 2 Capturementioning
confidence: 99%
“…A number of LCA studies were conducted on the coal‐fired power production facilities in the United Kingdom. Across the decades, several authors carried out partial or complete LCA of power stations with CCS technology and observed major reduction in terms of GHGs when compared to conventional fossil‐fueled power plants 20–26 . Limited researchers have studied the nationally environmental effects of CCS technology 27–32 .…”
Section: Introductionmentioning
confidence: 99%
“…This approach is common in such circumstances, given that LCA studies with similar characteristics have been conducted with the expectation of providing support for managerial decision-making processes and have been successful in their purposes. In this context, developments in the fields of the selection of productive arrangements for biofuel and derivative syntheses are highlighted [55,56], as well as closing water circuit [57][58][59], cattle raising [60], domestic solid waste management [61] and energy planning.…”
Section: Environmental Performancementioning
confidence: 99%